Key legal challenges and opportunities in the implementation of the Nagoya Protocol: The case of China. Issue 2 (7th March 2019) - Zheng, Xiaoou
Abstract : Since the Nagoya Protocol entered into force in 2014, the process of transposing international access and benefit‐sharing (ABS) standards into domestic contexts has been intensified in many countries. China became a party to the Nagoya Protocol in 2016. Being one of the mega‐biodiverse countries in the world, China nevertheless remains little known to international legal scholars of ABS‐related laws and regulations. This article aims to navigate this uncharted territory and examine the key legal challenges and opportunities in the process of implementing the Nagoya Protocol in China. Challenges with respect to the definition of key concepts, recognition of beneficiaries and potential approaches to benefit‐sharing are analysed in turn. Opportunities are investigated from both legal and institutional perspectives. The article proposes an integrated approach to legislate ABS under a comprehensive framework on biodiversity in order to sufficiently address the complexity and uniqueness of the Chinese national circumstances.